Are changes in physical activity during COVID-19 associated with mental health among Danish university students? - Petersen, Christina Bjørk; Krüger, Christina; Guldager, Julie Dalgaard; Algren, Maria Holst; Jervelund, Signe Smith; Berg-Beckhoff, Gabriele (Frontiers in Public Health, 2023)
Aims: The benefits associated with being physical active on mental health is well-established, but little is known on how rapid changes in physical activity are associated with mental health. This study investigated the association between changes in physical activity and mental health among Danish university students during the first COVID-19 lockdown. Methods: Online survey data were collected among 2,280 university students at the University of Southern Denmark and University of Copenhagen in May-June 2020 as part the “COVID-19 International Student Well-being Study”. Multiple linear regressions were used to analyze associations between changes in physical activity and mental health (depression and stress scores) adjusted for potential socio-economic confounders. Results: During the first COVID-19 lockdown, 40% decreased their moderate and 44% their vigorous physical activity, while 16% increased their moderate and 13% their vigorous physical activity. Overall, students with a stable physical activity level had the lowest mean depressive and stress scores. Adjusted analyses showed that a decrease in vigorous and moderate physical activity level was significantly associated with a higher depression score (mean difference (vigorous): 1.36, p<0.001 and mean difference (moderate): 1.55, p<0.001). A decrease in vigorous physical activity and an increase in moderate physical activity was associated with a 1-point increase in the PSS-4 stress score (p<0.001). Conclusion: A substantial proportion of students changed their physical activity level during lockdown. Our findings emphasize the importance of staying physically active during COVID-19 lockdown. This knowledge might be important for relevant health authorities to bridle post-pandemic mental health challenges.